Hardships of drugs monitoring – Ambiguities in pharmacovigilance (PV) rules 2018 and guidelines 2019 in the Pakistan - Nazish Abbas; Jabeen , Rawshan (Journal of the Pakistan Medical Association, 2021)
Introduction: Pharmacovigilance is the monitoring of drugs in and after post marketing surveillance phase of drug development and clinical trials. The phases in clinical trials is restricted to a certain population size under some conditions therefore all effects of medicine which is under trials is limited to the involved participants and it needs to be monitored through a constant channel later for eliminating the adverse events of drugs, when it is ready to be used by general consumers. In a country like Pakistan where self-medication and over the counter (OTC) medicine rate is already very high 25-75%, the regulations to control this health threat is weak due to the weak regulations. This paper is aimed to address the critical analysis on the pipeline draft of Pharmacovigilance Rules 2018 and Guidelines 2019 of Pakistan. Methodology and Rationale: The qualitative document analysis has been done by using National PV guidelines and Rules 2018 draft of Pakistan. The culture of reporting adverse events of medicines in Pakistan is not followed because of no awareness and no PV training of Pharmacists and Physicians in healthcare settings who could disseminate PV and understand the need of this hence. Pharmaceutical industries also do not adopt and accept this subject properly because of no regulations by the government and regulatory authorities. They do not have proper workforce and departments for PV. Continuous...